Determination of Red Blood Cell Distribution Width in Patients with Primary Cutaneous Vasculitis Compared to Systemic Vasculitis - Wahab, Farhana; Uddin, Mohammad Jamal; Asaduzzaman, ATM; Hena Chowdhury, Mohammod Abu; Mahmud, Hasan; Nasim, Rehnuma (Medicine Today, 2021)
Introduction: Red blood cell distribution width (RDW) has been considered as an inflammatory marker in various disorders. Evaluation of RDW value can also be used as a novel and additional marker for differentiating systemic vasculitis from primary cutaneous vasculitis. Objective: To compare RDW value between patients with cutaneous vasculitis with systemic vasculitis, thereafter to find out it's role as an effective indicator to distinguish both forms of vasculitis. Materials and Methods: This cross sectional observational study was conduct between from July 2016 to December 2017. Total of 48 patients were divided into primary cutaneous vasculitis and systemic vasculitis. Blood was collected in EDTA tube to measure RDW value. Patient’s disease activity also scored and plotted according to Birmingham vasculitis activity score. Statistical analysis was performed by using SPSS. Results: Significantly high mean RDW were found in patients with systemic vasculitis compared to primary cutaneous vasculitis (15.09±0.92 vs. 13.48±1.1, p = 0.000). BVAS was significantly greater (13.93±5.10 vs. 4.87±2.69, p = < 0.001) in systemic vasculitis as well as in patients with high RDW group (11.73±5.71 vs. 5.37±3.96, p = < 0.001). Optimal RDW cut off point for differentiating systemic vasculitis from cutaneous vasculitis was 14.2 with 81.3% sensitivity and 81.2% specificity. Conclusion: Present study revealed importance of RDW monitoring along with disease activity in patients with any form of vasculitis. Systemic vasculitis had higher level of RDW. So RDW can be considered as a marker to discriminate systemic vasculitis from primary cutaneous vasculitis. Medicine Today 2021 Vol.33(2): 84-89